Remapping the World in a Fifteenth-Century Cosmography: Genres and Networks Between Deccan India and Iran. Issue 2 (3rd July 2021) - Gupta, Vivek
ABSTRACT: This article examines codicological evidence for the presence of an illustrated Persian cosmography ( 'ajā'ib al-makhlūqāt ) (British Library Add 23564) at the fifteenth-century Bahmani court (1347–1538) of Deccan India. It traces this manuscript's itinerary from the dating of its colophon 1441, to its place in Bahmani Bidar, to a subimperial Mughal library, to its move to 'Adil Shahi Bijapur in 1618, and finally to its arrival at the British Library in 1860. It argues that distinguishing manuscript genre from textual genre when considering book production over a longue durée enables one to see books more clearly through the lens of their makers and readers. By establishing this cosmography's place in South Asia, this article enables it to be situated within the activity of this manuscript genre throughout the Deccan's early modern period.